2022
DOI: 10.3390/coatings12040432
|View full text |Cite
|
Sign up to set email alerts
|

Properties of SBS/MCF-Modified Asphalts Mixtures Used for Ultra-Thin Overlays

Abstract: In order to produce high-viscosity and high-toughness asphalt for ultra-thin overlays, the conventional asphalt cement was modified with high-content SBS and micro carbon fiber (MCF). The performances of the modified asphalt were studied by tests of penetration, softening point, ductility, kinematic viscosity, multiple stress creep recovery (MSCR), and by dynamic shear rheometer (DSR) and bending beam rheometer (BBR). Mixture properties were studied by tests of rutting, low-temperature bending, freeze–thaw spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In order to prolong the life cycle of ultra-thin overlays, it is recommended to use high-viscosity modified asphalt to improve its road performance. Therefore, the improvement of modified asphalt viscosity and mixture performance has been studied by many scholars [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prolong the life cycle of ultra-thin overlays, it is recommended to use high-viscosity modified asphalt to improve its road performance. Therefore, the improvement of modified asphalt viscosity and mixture performance has been studied by many scholars [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [22,23] conducted an experimental study on four different asphalt materials and found that the adhesion of the asphalt material to stone is the most important factor for improving the raveling resistance of pavements. However, current studies on preventive maintenance measures mainly focus on comparative performance analyses based on laboratory tests [24,25], a single comparative analysis of the pavement performance indicators [26], and identifying the optimal material composition of a certain VTAO through experimental investigation [25,27,28]. Comprehensive evaluation research on preventive maintenance measures has rarely been conducted.…”
Section: Introductionmentioning
confidence: 99%